ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP MITRA DALAM PERJANJIAN KERJA SAMA ANTARA PERUSAHAAN PENYEDIA APLIKASI MARKETPLACE (SHOPEE) DENGAN MITRA (KURIR) - Matara, Opa Jermias; Djaja, Benny (UNES Law Review, 2023)
This study aims to analyze the legal relationship in the agreement between the Shopee marketplace company and its partners (courier) and to analyze the legal protection for partners in the Cooperation Agreement between the Shopee marketplace company and partners (courier). The method used in this research is normative juridical, namely the study of legal norms, both primary and secondary legal materials. The results of the study show that the legal relationship in the agreement between the Shopee marketplace company and its partner (courier) is a pseudo partnership legal relationship, namely a cooperative relationship that is not balanced with one another, meaning that the relationship is not really mutually beneficial, instead burdening the courier. and contrary to the principle of partnership. In this case, partner status is intended as a way for companies to avoid the obligation to provide wages according to the regional minimum wage (UMR). Legal protection for partners in the Partnership Cooperation Agreement between the Shopee marketplace company and the partner (courier) is to guarantee that discrepancies or errors regarding the goods ordered are not the responsibility of the courier if this is not caused by the fault or negligence of the courier, as stipulated in Article 1708 KUH Civil. Losses suffered by the courier must be reimbursed and accounted for by the seller, if the discrepancy and damage to the goods from the start is the result of the seller's mistake, while the form of legal protection for the courier in the event of a cancellation of the goods order by the consumer is the first to take the mediation route between the consumer and the courier. disputing parties, if no settlement is reached, the dispute settlement will be pursued through legal means.